1995
DOI: 10.1111/j.1439-0418.1995.tb01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the strains of Trichogramma evanescens Westwood (Hym., Trichogrammatidae) collected from different hosts in Northern Maldova

Abstract: Biological and morphological characteristics together with electrophoretic patterns were compared for five strains of Triclzogramma ecanescens W., collected from the eggs of Mamestra brassicae L., Ostrinia nuhilulis Hb. and Agrotis segetum Schiff. in northern Maldova. Significant differences were observed in the biological characteristics including the proportion of female progeny, developmental period, longevity and fecundity. The strains also differed in the ratio of antenna1 hair length to the maximum width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
8
2
Order By: Relevance
“…Following host acceptance, the parasitising female starts oviposition, and this step is strongly depending on temperature. The range of parasitised eggs of S. cerealella at 27 • C was 17.4 and 25.5 with five strains from Moldavia (Ram et al, 1995). The temperature dependence of parasitism of T. cacoeciae was found to be similar compared with those species.…”
Section: Discussionmentioning
confidence: 85%
“…Following host acceptance, the parasitising female starts oviposition, and this step is strongly depending on temperature. The range of parasitised eggs of S. cerealella at 27 • C was 17.4 and 25.5 with five strains from Moldavia (Ram et al, 1995). The temperature dependence of parasitism of T. cacoeciae was found to be similar compared with those species.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore food availability in the habitat aVects survival and parasitization rates (Zhang et al 2004;Romeis et al 2005) and diVerent strains of the same species may show distinct host preferences (Van Dijken et al 1986;Ram et al 1995). Therefore Smith (1996) and Wührer (1996) propose that the four main factors, i.e.…”
Section: Introductionmentioning
confidence: 97%
“…TE parasitoid was extensively used in inundative releases against a number of lepidopterous pests of several crops (e.g., corn, rice, sugarcane, cotton, fruit trees, grape, etc.) (Ram et al 1995;El-Wakeil et al 2008), but had not been observed in olive groves. Releases of TE wasps were carried out in an olive farm that represent a young and large intensively managed plantations under arid weather condition and TE free.…”
Section: Discussionmentioning
confidence: 80%
“…These species/strains had not been collected from olive groves, but some of them were successfully used in other crop systems. TE wasps are known to attack a wide variety of field crop moths (Abbas et al 1987;Ram et al 1995;Bayram and Kornosor 1999;Herz et al 2005). TE parasitoid was extensively used in inundative releases against a number of lepidopterous pests of several crops (e.g., corn, rice, sugarcane, cotton, fruit trees, grape, etc.)…”
Section: Discussionmentioning
confidence: 99%